Primulina lianchengensis (Gesneriaceae), a new species from Danxia landform of Fujian, China: Evidence from morphological and molecular analyses - Ye, Bao-Jian; Chen, Xin-Yan; Zheng, Shi-Qun; Wang, Li-Hui; Chen, Hui; Chen, Shi-Pin (Phytotaxa, 2019)
Primulina lianchengensis B.J.Ye & S.P.Chen (Gesneriaceae) is described and illustrated from Fujian Province in the Southeast of China. Then phylogenetic analyses of the genus were presented using nuclear ribosomal ITS and two plastid markers (atpB-rbcL and rpL32-trnL). Morphological analysis indicates that P. lianchengensis is similar to P. danxiaensis, P. depressa, P. lechangensis and P. yangshanensis, but it differs in the base and margin of leaf, petiole, bract, length and shape of corolla, numbers of staminodes and stigma lobe. Molecular analysis reveals that P. lianchengensis is genetically similar to P. danxiaensis and P. yangshanensis.